A critical evaluation of pre- and post- 1994 large-scale development programmes in South africa with particular focus on employment creation - Thwala, Wellington Didibhuku (My University, 2010)
In South Africa, the levels of unemployment and poverty are extremely high and these are two of South Africa’s most pressing problems. Over the past 28 years several major programmes have been initiated in South Africa to counter unemployment and poverty. Between 1980 and 1994, the former government spent billions of Rands on large-scale development programmes with the stated objective of using labour-intensive methods during the provision of physical infrastructure, to create employment and alleviate poverty. However, this did not solve the unemployment problem. Since 1994 the African National Congress (ANC) government has implemented large-scale programmes with similar objectives to those before 1994. After an analysis of the theoretical premises and implementation of labour-intensive public works programmes in Africa, the thesis critically evaluated several pre - and post - 1994 large-scale development programmes in South Africa. Major conclusions are that very little sustainable employment was created and there was no long-term programme approach to address poverty alleviation. Furthermore, lessons that could have been learnt from pre – 1994 have not been applied in the post 1994 period. Shortcomings in programme planning and implementation of large-scale development programmes in South Africa still exist. Another major conclusion is that the pre-1994 lessons were not taken into considerations in the post-1994 programme planning and implementation. Based on the research, the author has derived a six phase Programme Management Framework for Development Programmes. This framework embodies a long-term programme management approach to the planning and implementation of large-scale, labour-intensive development programmes.
Keywords: Employment creation; Infrastructure; Public works; Large-scale development programmes projects